ANALISIS PENGARUH PEMBANGUNAN INFRASTRUKTUR TERHADAP PENANAMAN MODAL ASING LANGSUNG DI WILAYAH INDONESIA - Manuaba, Ida Bagus Riski Putra; Saskara, Ida Ayu Nyoman (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2022)
Infrastructure is a reflection of a country in running its economy, if a country's infrastructure is weak, it can be ascertained that the economy running in that country is running inefficiently. The objectives of this study include (1) To find out road construction, development of information and telecommunications technology, and the number of transportation facilities will have a partial effect on FDI in every province of Indonesia. (2) To find out road construction, development of information technology and telecommunications, and the number of transportation facilities will have a simultaneous effect on PMA in every province of Indonesia. The data used is secondary data obtained from BPS, with a total of 5 years of observations. The analysis technique used is multiple linear analysis technique. The results show that (1) the number of roads has a positive and significant effect on foreign investment in Indonesia. (2) IP-TIK has a positive and significant effect on foreign investment in Indonesia. (3) The number of motorized vehicles has a positive and insignificant effect on foreign investment in Indonesia.   Keywords: Foreign Investment, Road Construction, Information and Communication Technology Development Index, Number of Motorized Vehicles